EMPTY NEST PADA LANSIA DITINJAU DARI TINGKAT GRATITUDE DI KARANGANYAR - Sari, Theresia Novi Pamungkas; Karyanta, Nugraha Arif; Widyastuti, Endang (Jurnal Psikohumanika, 2023)
The ederly is the last stage in human life. In this phase, the elderly experience a variety of life processes, one of them is empty nest. Children where leave the house cause them to feel empty. As a result, the elderly experience difficulties in their lives. The purpose of this study was to determine the effect of gratitude on loneliness in the elderly. Based on the literature review, the researchers determined the research hypothesis that there was a negative relationship between gratitude and loneliness. This research used quantitative methods and used quota sampling as a sampling technique. The subjects in this study were 54 elderly IPPK (Ikatan Purnakaryawan Pendidik dan Kebudayaan) members where live in the sub-district of Jumapolo. Research variables were measured using gratitude scale and empty nest scale. The obtained data were analyzed using simple product moment analysis. The results showed the value of correlation coefficient of = -0,352 p= 0,019 (p<0,01). It proved that there was a significant negative correlation between gratitude and empty nest in the elderly, so hypotheses presented in this study was received. Additional analysis using multiple regression analysis was used to test the influence between aspects of gratitude and empty nest. Based on the calculation results, a significance value of p = 0.69 (not significant) (p> 0.05) was obtained. The results of the multiple regression analysis show that there is no influence between the gratitude aspect and the empty nest.